The whale barnacle Cryptolepas rhachianecti (Cirripedia: Coronulidae), a phoront of the grey whale Eschrichtius robustus (Cetacea: Eschrichtiidae), from a sandy beach in The Netherlands - Bosselaers, Mark; Collareta, Alberto (Zootaxa, 2016)
An isolated compartment of a whale barnacle is herein described from Recent beach deposits in Zoutelande (Walcheren, The Netherlands). This specimen is identified as belonging to the extant coronulid species Cryptolepas rhachianecti, currently known as an epizoic symbiont of the grey whale Eschrichtius robustus. This find represents the first occurrence of C. rhachianecti outside the North Pacific, and the first one as a (sub)fossil. In view of the fact that E. robustus, which is currently confined to the North Pacific, is known as a subfossil from the northeastern Atlantic between late Late Pleistocene (c. 45,000 years ago) and historical (c. 1700 AD) times, we propose a similar (late Quaternary) age for the isolated compartment. The find indicates that the extinct late Quaternary northeastern Atlantic population of E. robustus was infected by Cryptolepas rhachianecti. Our find is, therefore, compatible with the hypothesis of an ancient grey whale migration route running between the subtropical/temperate waters of the northeast Atlantic (or Mediterranean Basin), and the cold waters of the Baltic Sea (or southern Arctic Ocean), through the southern North Sea. Finally, we discuss the systematic placement of the fossil barnacle species Cryptolepas murata and propose the possibility of its removal from the genus Cryptolepas pending further investigations.